Screening dan Penentuan Status Gizi Serta Upaya Promosi Pencegahan Stunting, Wasting dan Obesitas - Riadi, Ahmad; Hadipranoto, Ichsan; Lestari, Tri Wiji (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the prevalence of stunting, obesity, and wasting in toddlers. The research method used is quantitative with a descriptive approach. The results of the study showed that the number of toddlers who experienced Good Nutrition was 172 (78,5%), stunting 67 children (30,6%), wasting 12 (5.5%), and obesity 7 (3.2%). It was concluded that although most toddlers have normal nutritional status, cases of stunting and wasting still occur frequently. This study emphasizes the importance of regular monitoring of child growth, especially for families with toddlers, to ensure early detection and intervention. Keywords: Obesity, Stunting, Wasting